Sistem Informasi Pengarsipan Berbasis Animasi 3D Di Lembaga Pendidikan Komputer Pratama Mulia Surakarta - Arif Sutikno -Politeknik Pratama Mulia Surakarta; Estiarto Wahyu Sumirat - Universitas Surakarta; Haryani - Universitas Surakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
ABSTRACT : Pratama Mulia Surakarta Computer Course complain that the Existed ArchievingSystem they owned not in proportion, closed, undevelopable and become to failure. According tosystem life cycle principles, the management have to plan for a new one as an expected system. Sothe problem are : “Is it right that the existed system not in proportion, closed, undevelopable andbecome to failure?, how to design an expected system to replace and eliminate the weakness of theexisted one?” The goals of this scripts are : The first is “Prove that the existed system is not inproportion, closed, undevelopable and become to failure”, the second is “Build an expected systemcalled 3D Animation Based Archieving System of Pratama Mulia Surakarta to eliminate the weaknessof existed system”, the third is “Create a prototype of application for computer system that will beapplied as an sub-system of this system”, and the fourth is “Create a system implementation planning”.The usage of methodology to solve the problem are “Observe with questionairing supportedby interviewing, system analysis and design” taken from Kendall and Kendall theory to get theunderstanding of existed system, “feasibility study” with feasibility impact grid taken from Kendall andKendall theory, and “Implementation planning theory” taken from the book writen by Suryadi, H.S. andBunawan. After the subjects above already done, this script reports that it is true and proved that theexisted system is not in proportion (means not all of the goals accomplished by the system), closed,undevelopable and become to failure (means going to or disposed towards failure), an expectedsystem to replace and eliminate the weakness of the existed system it’s already done and ready toimplement for Pratama Mulia Surakarta Computer Course.Keyword : computer, computer technology, archieve, archieving, 3D Animation.Abstraksi: Pratama Mulia Surakarta Kursus Komputer mengeluh bahwa Archieving Sistem Eksismereka dimiliki tidak sebanding, ditutup, dapat dibangun dan menjadi kegagalan. Menurut prinsipprinsipsiklus hidup sistem, manajemen harus merencanakan untuk yang baru sebagai suatu sistemyang diharapkan. Jadi masalahnya adalah: